2020
DOI: 10.1364/ao.388313
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-compensated infrared-based low-cost mobile platform module for mass human temperature screening

Abstract: As fast human temperature screening is needed in large public areas, this paper proposes a low-cost mobile platform module that combines the advantages of analyzing visible and thermal images. In particular, the key idea relies on face detection in the visible image. Then the coordinates of all faces detected are mapped on to the thermal image to determine their corresponding temperatures. Internal temperature compensation and external reference temperature also are employed to reduce the unwanted temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The IRT experiments found in this review reported sensitivity values between 15% and 100%. However, it should be noted that the studies that reported 100% sensitivity used NCIT systems as the reference [41]. The highest sensitivity for a study using a contact-based reference was 91% [42].…”
Section: Resultsmentioning
confidence: 99%
“…The IRT experiments found in this review reported sensitivity values between 15% and 100%. However, it should be noted that the studies that reported 100% sensitivity used NCIT systems as the reference [41]. The highest sensitivity for a study using a contact-based reference was 91% [42].…”
Section: Resultsmentioning
confidence: 99%
“…IRT can be used to quickly screen the body temperature of large groups of people. For example, Armote Somboonkaew's research shows that IRT can screen the body temperature of nine people simultaneously at a speed of eight frames/second [49]. A correlation coefficient of 0.731 was found between IRT and forehead skin thermometers.…”
Section: Discussionmentioning
confidence: 99%
“…However, these models do not scale well, and there is a high risk of bias that raises concerns to be used in daily practice. To mitigate this, [32], use multiple sensors to improve accuracy. Various methods to fuse different algorithms have also been explored in [24,25].…”
Section: Ai Models For Covid Prognosis and Diagnosismentioning
confidence: 99%